2018
DOI: 10.1038/s41467-018-06708-x
|View full text |Cite
|
Sign up to set email alerts
|

Raising the redox potential in carboxyphenolate-based positive organic materials via cation substitution

Abstract: Meeting the ever-growing demand for electrical storage devices requires both superior and “greener” battery technologies. Nearly 40 years after the discovery of conductive polymers, long cycling stability in lithium organic batteries has now been achieved. However, the synthesis of high-voltage lithiated organic cathode materials is rather challenging, so very few examples of all-organic lithium-ion cells currently exist. Herein, we present an inventive chemical approach leading to a significant increase of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
160
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(185 citation statements)
references
References 73 publications
10
160
1
1
Order By: Relevance
“…Sections 3.3.1, 3.5, and 3.6.1, respectively) proved to be promising candidates. Consequently, the number of fully organic approaches is increasing, and several working all‐organic cells were presented (Table ) during the last years, revealing relatively high voltages, capacities, and stabilities …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sections 3.3.1, 3.5, and 3.6.1, respectively) proved to be promising candidates. Consequently, the number of fully organic approaches is increasing, and several working all‐organic cells were presented (Table ) during the last years, revealing relatively high voltages, capacities, and stabilities …”
Section: Discussionmentioning
confidence: 99%
“…Notably, the amorphous form revealed a much better performance compared to the crystalline ones. Poizot and co‐workers utilized a 2,5‐dihydroxyterephthalate with one magnesium and two lithium cations per molecule in a lithium‐organic cell, which featured a moderate capacity of 80 mAh g −1 , remaining stable over at least 80 cycles . Subsequently, the authors applied the material in an all‐organic, Li + ‐based, and symmetric cell, exploiting the carboxylate‐ as well as the quinone‐based redox processes of the compound (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…The energy density of this full cell could perhaps not be competitive with LIBs, and it is mainly limited by the relatively low sodiation plateau of organic cathodes (most 2.0–3.0 V). Fortunately, this issue could be improved by some modifications such as cation substitution, according to the significant work by Poizot and co‐workers . The desodiation plateau of the anode could also be modulated by introduction of various functional groups with different electronic effects .…”
Section: Figurementioning
confidence: 99%
“…To tackle this issue, many approaches have been attempted, [ 8,9 ] and it is found that rational molecular structure design plays important roles in improving its performance. [ 7,10–21 ] In fact, to reduce the solubility of organic molecules, the key is to strengthen intermolecular interaction. The simplest way is to introduce substituent(s) into BQ to increase the intermolecular van der Waals force or ion interaction (Figure S1a, Supporting Information).…”
Section: Introductionmentioning
confidence: 99%